2008
DOI: 10.1002/anie.200803647
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Asymmetric Aziridination of Enones

Abstract: The development of novel and efficient catalytic methodologies for the stereoselective preparation of chiral aziridines is an important synthetic target.[1] Aziridines constitute a key structural feature of several classes of natural products and are extremely versatile building blocks that can undergo synthetically useful transformations.[2] The catalytic asymmetric aziridinations of olefins provide direct and useful access to such a valuable scaffold, and great efforts and progress have been made in this fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(54 citation statements)
references
References 42 publications
(14 reference statements)
1
53
0
Order By: Relevance
“…The authors claim the most interesting feature of this reaction is that, conversely from most of the reactions described in this review, the catalytic couple is not formed by an amine and an acid, but by two amines. A couple between a Cinchona alkaloid derivative and an aminoacid has already been used by other research groups and examples have also been reported in this review, too [63,81,85,86]. However, in previous reports, Cinchona alkaloid derivatives act as the catalysts and drive the enantioselectivity, whereas aminoacid sometimes improves the general efficiency of the catalyst trough matched/mismatched combinations.…”
Section: Diels-aldermentioning
confidence: 84%
See 1 more Smart Citation
“…The authors claim the most interesting feature of this reaction is that, conversely from most of the reactions described in this review, the catalytic couple is not formed by an amine and an acid, but by two amines. A couple between a Cinchona alkaloid derivative and an aminoacid has already been used by other research groups and examples have also been reported in this review, too [63,81,85,86]. However, in previous reports, Cinchona alkaloid derivatives act as the catalysts and drive the enantioselectivity, whereas aminoacid sometimes improves the general efficiency of the catalyst trough matched/mismatched combinations.…”
Section: Diels-aldermentioning
confidence: 84%
“…Moreover, the catalyst for the reaction is an amino acid-Cinchona alkaloid salt and both the pseudo-enantiomers of the catalyst (73 and 73', the same as 56 with different counterions) are available, so both optical antipodes of the aziridine can be prepared (Scheme 21) [85,86].…”
Section: Scheme 17mentioning
confidence: 99%
“…To the best of our knowledge, such a reaction for this class of compounds has not yet been described. As mentioned previously, the organocatalytic aziridination of cyclic enones has only been rarely described, whereas acyclic enones have been studied more frequently (35,36). Differently substituted hydroxylamine derivatives were tested as nucleophilic reagents, in which the hydroxy functionality serves as the leaving group and enables therefore the formation of the three-membered heterocycle after the nucleophilic 1,4-addition of the amine moiety.…”
Section: Resultsmentioning
confidence: 99%
“…The described reactions are enabled by an enantioselective enone epoxidation/aziridination-Wharton-reaction sequence. While the organocatalytic epoxidation of cyclic and acylic enones has been recently described by List et al (32,33) and Deng et al (34), the organocatalytic aziridination of enones has been mainly limited to acyclic substrates (35,36). We envisioned that a merger of the catalytic enone functionalizations with the hydrazine mediated 1,3-transposition following the Wharton protocol (37) could allow simple access to a broad spectrum of optically active allylic products under metal-free conditions, and preferably in an one-pot process (Scheme 2).…”
mentioning
confidence: 99%
“…Salt 12 (20 mol%) was able to promote the aziridination of aliphatic and aromatic α,β-unsaturated ketones, using tosylated carbamate 11a and NaHCO 3 as base at room temperature, yielding the corresponding aziridines 13 in high yields, diastereo-and enantioselectivities (Scheme 3) [18]. The reaction seemed to be tolerant to steric and electronic demands on the starting poor olefin systems.…”
Section: Methodsmentioning
confidence: 99%